PELAKSANAAN TRADISI BETANGAS SEBELUM PERKAWINAN ETNIK MELAYU DI DESA SUNGAI RAYA KABUPATEN BENGKAYANG - Sutrisni, Sutrisni; Bahari, Yohanes; Ramadhan, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to describe the procession and meaning contained in the implementation of the betangas tradition before ethnic Malay weddings in Sungai Raya Village, Sungai Raya Islands District, Bengkayang Regency. Researchers used descriptive qualitative methods. Data collection techniques are observation, interviews and documentation. Data analysis techniques are data reduction, data presentation, drawing conclusions and verification. This data is presented descriptively using 4 informants. The research results show that the procession in the betangas tradition in Sungai Raya Village is divided into 3, namely the initial process, the core process, and the end. The initial process is preparing the specified tools and materials. The core process is that all the ingredients are put into a pot filled with water while a mantra is read, then boiled until it boils, then the bride and groom are placed on a mat in a sitting position with the boiled water. The final process is that the village shaman bathes the bride and groom with water and a mantra is recited. The meaning contained in the betangas tradition is found in the ingredients used in the boiled water such as the buds of sui, citronella leaves, pandan leaves, and ylang-ylang flowers.